Oral health education among Portuguese adolescents - Veiga, Nélio Jorge (2015)
Introduction: Oral health education is an important issue that should be given to children and adolescents, allowing the acquisition of correct oral health behaviours. The objective of this study was to determine the prevalence and assess the quality of oral health behaviours among a sample of portuguese adolescents and verify their association with socio-demographic variables. Participants and methods: A cross-sectional study was designed with a sample of 447 adolescents aged 12 to 19 years old, attending a public school in Satao, Portugal. An interview was made questioning about socio-demographic factors and oral health behaviours to each adolescent in the classroom. Prevalence was expressed in proportions and crude odds ratio (OR) with 95% confidence intervals (CI) were used to measure the strength of association between oral health behaviours and socio-demographic factors. Results: The prevalence of toothbrushing (twice-a-day or more) was 90.6%. Five point eight percent of adolescents reported daily flossing, more frequent among female gender (female, OR=2.03 95% CI=1.35-3.05) and adolescents older than 15 years (>15years, OR=1.90 95% CI=1.24-2.92). Sixty-seven percent had at least one dental appointment in the previous twelve months. The prevalence of dental appointments was associated with socio-economic variables such as the father's professional situation (unemployed, OR=0.33 95% CI=0.17-0.65) and crowding index (>1,OR=0.495%CI=0.16-0.98). Conclusion: Considering the results of the present study, oral health community programs and primary preventive strategies, such as improvement of oral health education in schools should be considered in order to reduce the risk level of oral diseases and develop better oral health behaviours. (C) 2015 Published by Elsevier Ltd.